Co‐transplantation of mesenchymal stromal cell and haploidentical hematopoietic stem cell with TCR αβ depletion in children with primary immunodeficiency syndromes. (19th August 2021) - Atay, Didem; Akcay, Arzu; Akinci, Burcu; Yenigurbuz, Fatma Demir; Ovali, Ercument; Ozturk, Gulyuz
Abstract: Background: Haploidentical HSCT is a good option for children with PIDs lacking an HLA‐matched donor. Co‐transplantation of MSCs during haploidentical HSCT in patients with PIDs may enhance engraftment, decrease the risk of GVHD, and ensure stable donor chimerism. Methods: Twenty‐seven pediatric patients (median age, 1.4 years; range, .3–10.9) with PIDs undergoing thirty haploidentical HSCT with TCR αβ depletion and co‐transplantation of MSCs were enrolled to study. Most patients (73.3%) received myeloablative conditioning consisting of treosulfan or busulfan, fludarabine, and thiotepa. The median duration of follow‐up was 14.3 months (range, 1–69 months). Results: Acute GVHD occurred in 7 patients (grade I‐II n = 5, grade III‐IV n = 2). Chronic GVHD was observed in only one patient. Twenty‐one patients (70.2%) had 100% donor chimerism in all cell lines including T‐cell and B‐cell lineages. Primary graft failure was observed in 7 patients (25.9%). The cumulative incidences of TRM were 20% at day 100, and 26.7% at one year and five years. Probabilities of OS were 80% at day 100, and 71.9% at 1 year and 5 years. Infants transplanted younger than 6 months of age had the highest 5‐year survival rate (85.7%). Conclusion: We conclude that use of TCR αβ depleted haploidentical transplantation with MSCs may ensure a rapid engraftment rate, low incidence of significant acute and chronic GVHD, and acceptable post‐transplantation morbidity, especially in patients diagnosed with SCID and may be considered in children with PIDs. In younger patients (≤6 months), survival is comparable between HLA‐matched graft and CD3+ TCRαβ depleted HLA‐mismatched graft recipients.